Respuesta :

Looks like the claim is

(2 tan(x) - sin(2x)) / (2 sin²(x)) = tan(x)

Recall the double angle identity for sine:

sin(2x) = 2 sin(x) cos(x)

as well as the definition of tangent:

tan(x) = sin(x) / cos(x)

Then on the left side, we can cancel factors of 2 sin(x) to get

(2 sin(x) / cos(x) - 2 sin(x) cos(x)) / (2 sin²(x))

= (1/cos(x) - cos(x)) / sin(x)

Multiply this by cos(x)/cos(x) :

(1/cos(x) - cos(x)) / sin(x) = (1 - cos²(x)) / (sin(x) cos(x))

Recall that for all x,

sin²(x) + cos²(x) = 1

so that

(1 - cos²(x)) / (sin(x) cos(x)) = sin²(x) / (sin(x) cos(x))

= sin(x) / cos(x)

= tan(x)

as required.